The development and test of the learning environment scale from the perspective of China’s engineering education certification - Jing, Bian; Xiaofeng, Ren (Frontiers in Education, 2025)
The learning environment has been transformed from a teaching background to the core educational technology in contemporary engineering education. The learning environment that meets the engineering education certification standards is conducive to the standardization of teaching and the realization of educational goals. However, the correlation between the existing learning environment scale and the professional certification standard is insufficient. Especially in China, there are few studies on the learning environment scale based on engineering education professional certification. The research adopts the mainstream learning environment evaluation perspective of students’ perception evaluation, and combines curriculum learning, teachers and student relationship, classmate relationship, learning atmosphere, institutional environment, project and practice, physical resources, and so on seven factors. The graduation requirements of engineering education certification in China are deeply coupled with the content of the benchmark, and the quality of the systematic questionnaire is tested. The results show that the engineering education learning environment scale has a robust seven-factor structure, reasonable 36 items, good reliability and validity, no common method deviation, and the constructed model is appropriate. It can be used as a learning environment measurement tool to support graduation requirements. The innovation of the future learning environment should not only be based on the standard of engineering education certification graduation requirements, but also support graduates to become a new generation of engineers with a global vision and sustainable development leadership.